Effects of sunlight and shadow on the surfaces of pigeon towers in Central Asia: Case studies in Iran, Qatar, Egypt and Saudi Arabia - Momeni, Kourosh; Shiri, Tohid (Journal of Architecture and Urbanism, 2022)
In many parts of the world, especially Central Asia, pigeon towers have been constructed as traditional buildings with different forms and types to keep pigeons. These buildings are cylindrical, cubic, dome-like and multi-cylinder in shape. This study was conducted to identify the effects of sunlight and shadow on the surfaces of pigeon towers in Iran, Qatar, Egypt, and Saudi Arabia with hot and dry or humid climates. Several pigeon towers with different types and structures in these countries were selected and modeled in detail in Rhino 5. Radiance and Ecotect were then employed to measure solar radiation and shadow on the surfaces of the pigeon towers on the hottest day of the year. According to the graphical and numerical results obtained, sunlight and shadow differently affected the surfaces of the different pigeon towers. The effect level of sunlight and shadow on the single-form pigeon towers was higher than on the vaults. In fact, solar radiation was lower and shadow was higher per square meter of the surfaces of the vaults constructed as pigeon towers in close proximity. These houses were therefore found to be the optimal type for the hot and dry or humid climate in Central Asia.